Geotouristic attractions of the Danakil Depression - Cieśluk, Katarzyna; Karasiewicz, Mirosław T.; Preisner, Zdzisław (Geotourism/Geoturystyka, 2014)
Geotourists and unconventional tourists will be definitely interested in the Danakil Valley. It is rarely visited place but absolutely extraordinary in many ways. It is in an area of divergence of lithosphere plates and, therefore connected to that, seismic andvolcanic activity can be observed. Stunning terrain forms, geologicalstructures, colours and diversity seem to be unreal. This desert is very inhospitable due to poisonous exhalations, omnipresent salt, an extremely hot climate, water deficiency and the fact that fauna and flora don’t exist here. Despite all of these inconveniences, theDanakil Valley is inhabited by the Afars, a population thriving mainly on primitive salt production. Their rare culture is worth attention too. Not so long ago they were hostile and even now nativescan be unpredictable and dangerous. Additionally, visitors should remember other difficulties: legal, organisational, financial and, above all, natural and climatic ones.